COVID-19 vaccines based on viral nanoparticles displaying a conserved B-cell epitope show potent immunogenicity and a long-lasting antibody response - Affonso de Oliveira, Jessica Fernanda; Zhao, Zhongchao; Xiang, Yi; Shin, Matthew D.; Villaseñor, Kathleen Elizabeth; Deng, Xinyi; Shukla, Sourabh; Chen, Shaochen; Steinmetz, Nicole F. (Frontiers in Microbiology, 2023)
The COVID-19 pandemic caused by SARS-CoV-2 sparked intensive research into the development of effective vaccines, 50 of which have been approved thus far, including the novel mRNA-based vaccines developed by Pfizer and Moderna. Although limiting the severity of the disease, the mRNA-based vaccines presented drawbacks, such as the cold chain requirement. Moreover, antibody levels generated by these vaccines decline significantly after 6 months. Additionally, the approved vaccines were mostly designed to target the receptor binding domain (RBD) or full-length spike (S) glycoprotein of SARS-CoV-2, which do not cover new variants of concern, creating a demand for adjusted formulations and booster campaigns. To overcome these challenges, we have developed COVID-19 vaccine candidates based on the highly conserved SARS CoV-2 809-826 B-cell peptide epitope (denoted 826) conjugated to cowpea mosaic virus (CPMV) nanoparticles and bacteriophage Qβ virus-like particles, both platforms have exceptional thermal stability, facilitate epitope delivery with inbuilt adjuvant activity. We evaluated two administration methods: subcutaneous injection and an implantable polymeric scaffold. Mice received a prime–boost regimen of 100 μg per dose (2 weeks apart) or a single dose of 200 μg administered as a liquid formulation, or a polymer implant. Antibody titers were evaluated longitudinally over 50 weeks. The vaccine candidates generally elicited an early Th2-biased immune response, which stimulates the production of SARS-CoV-2 neutralizing antibodies, followed by a switch to a Th1-biased response for most formulations. Exceptionally, vaccine candidate 826-CPMV (administered as prime-boost, soluble injection) elicited a balanced Th1/Th2 immune response, which is necessary to prevent pulmonary immunopathology associated with Th2 bias extremes. While the Qβ-based vaccine elicited overall higher antibody titers, the CPMV-induced antibodies had higher avidity. Antibody titers indicated that the immunogenicity of our candidates is comparable to a mRNA-RBD vaccine according to an open-source end-point titer data – albeit a drop in titers was not observed over a one-year time frame. Regardless of the administration route and formulation, our vaccine candidates maintained high antibody titers for more than 50 weeks, confirming a potent and durable immune response against SARS-CoV-2 even after a single dose.